Artificial breeding and embryonic development of Synodontis zambezensis (Peters, 1852). (8th July 2018) - Volschenk, Claire Michelle; Tweddle, Gavin Paul; Janse van Vuren, Johannes Hendrik; Greenfield, Richard
Abstract: Synodontis sp . are an important source of food in many African countries including, Nigeria, South Africa, Egypt and Ghana. This is likely due to the genus being an excellent source of fat in fish‐based diets. However, there is also increased accumulation of lipophilic pollutants which can be transferred to the human population. In South Africa, Synodontis zambezensis is an important food source in rural communities, particularly along the Phongolo River system. The aim of this study was to breed Synodontis zambezensis in captivity, adapting a variety of protocols previously used in artificial breeding of Clarias gariepinus, Synodontis petricola and Synodontis nigromaculatus . A synthetic gonadotropin‐releasing hormone compound (Aquaspawn®) was used to induce reproductive development followed by manual fertilization of stripped eggs using sperm from dissected testis of sacrificed males. The embryonic development was consistent with other fish species and followed the same embryonic developmental stages. Initial hatching occurred within 26 hrs after fertilization, and survival rates of fry and subsequent fingerlings were as high as 80%. S. zambezensis has previously been used as a bio‐indicator species in field studies. Successful artificial breeding and rearing of this species improves the ability to use this indigenous species as a test organism in laboratory‐based assessments of chemicals and bioaccumulation of harmful chemicals such as Dichlorodiphenyltrichloroethane (DDT).